CHARECTERISTICS OF ON-STREET PARKING IN ISTANBUL - Algburi, Thaier Fadhil Salman; Ozen, Halit (YILDIZ TECHNICAL UNIV, 2017)
On-street parking in city centers is an attractive option for drivers because of the accessibility and the closeness to the commercial areas, markets, shopping centers etc. On-street parking is defined in literature as the vehicles parked on the sides of the street itself. On-street parking leads to reduction in the capacity of the roadway due to the occupation of the lane, parking maneuvers and the effects it makes on the other lanes. The time spent by the vehicles while maneuvering to enter and leave the parking, type of the parking and the duration of the parking were observed in Yildiz Technical University Traffic Management Center (YTU-TMC). Using these data, traffic count was conducted and then the possibility of parking for any vehicle passing through the area was computed. The data were collected at the peak periods which are between 11:30 AM -14:30 PM and 17:00 PM -20:00 PM for the each direction of the roadway. Monte Carlo simulation was implemented to find out the possibility of parking using the data. The results of the study clearly indicate that the commercial center is considered as one of the most important factors that plays role in increasing the possibility of parking. Parking between two parked vehicles takes more time than the other parking types. Monte Carlo simulation can be used to find out the probability of parking for all parking types.
Keywords: On-street parking; maneuver time; Monte Carlo simulation; parking maneuver; Engineering